Editorial Tips on Publishing Qualitative Research in Medicine & Healthcare - Warren Bareiss (Qualitative Research in Medicine & Healthcare, 2023)
Welcome to Issue 3, Volume 6 of Qualitative Research in Medicine in Healthcare. The term “qualitative research” covers a wide range of theories and methodologies, and this issue certainly illustrates that diversity of approaches. As with most articles published in QRMH, authors featured in this issue worked through multiple manuscript iterations prior to acceptance for publication. Many other submitted manuscripts, of course, never make it that far. No doubt the story is the same for any reputable research journal. [...]